The evolution of ethics in America : standards born of crisis - French, Laurence, 1941- (New York , NY : Routledge, 2021)
"In this book, Laurence Armand French frames the emergence of medical, clinical, and legal ethical standards within the long history of institutional and systemic racial and gender biases in the United States. He explores the role that White privilege and elitism play in justifying long-held discriminatory practices ranging from the eugenics crusade a century ago to the #MeToo and Black Lives Matter (BLM) movements of today. The book identifies and analyzes events highlighting systemic racism in the United States and explores how these events were exacerbated during the presidency of Donald J. Trump. The evolution of ethical standards in the United States is a reaction to long-held practices that discriminate against certain classes of people based on gender, age, and race and ethnicity. The White supremacist world view contributed to systemic biases that directly affect people of color as well as women, and those biases, in turn, are inherent components of the social structure of economic, academic, and judicial institutions. This process impacts both procedural and social justice, the very foundation of ethical standards of which our Constitution is based. This work attempts to unravel the social and psychological aspects of human behavior contributing to this phenomenon. This concise yet comprehensive book is a valuable resource to a broad audience, including students of criminal justice, as well as scholars, researchers, and professionals in both the social and physical sciences"--
OCLC-licensed vendor bibliographic record.
Keywords: Ethics -- United States -- History; SOCIAL SCIENCE / Criminology